SISTEM INFORMASI AKUNTANSI PENENTUAN HARGA POKOK PRODUKSI DENGAN METODE JOB ORDER COSTING SEBAGAI PENENTU HARGA JUAL BERBASIS WEB - Sri Wahyuning Wahyuning; Nofi Khayati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
Accounting Information System is a system that provides an information technology-based accounting process. Determination of the cost of production in a company requires the right method, because the cost of production is one of the factors that can influence the determination of the selling price. The cost of production is also used to determine the magnitude of the profits obtained by the company.Manufacturing company which is a company engaged in the process of raw materials into finished goods, requires basic materials that are used as the main ingredients in the production process.This study aims to determine how the application of the Job Order Costing method is a method of collecting production costs to determine the cost of production at the company on the basis of orders. The method used in this study uses a research and development (R&D) model, which is the method used to produce certain products, and test the effectiveness of the product. In this study using the PHP programming language and MySQL for the database